49‐2: Distinguished Student Paper: High‐Efficiency Switchable Optical Elements for Advanced Head‐up Displays. Issue 1 (29th May 2019) - Zhan, Tao; Lee, Yun-Han; Xiong, Jianghao; Tan, Guanjun; Yin, Kun; Yang, Jilin; Liu, Sheng; Wu, Shin-Tson
Abstract : The Pancharatnam‐Berry phase optical elements (PBOEs) are utilized to enhance the performance of head‐up displays (HUDs). The PB lenses provide varifocal functionality, while the PB deflectors can function as optical combiners and waveguide couplers. Rigorous coupled wave analysis based on scattering matrix is also developed and applied for structure optimization.